Isolation of A Molybdenum-reducing Bacillus sp. strain Zeid 15 and Modeling of its Growth on Amides (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2021)
More and more people are looking at bioremediation as a cheaper option to physhiochemical techniques for cleaning up pollution from farming, mines, and other chemical industries. Toxic effects of molybdenum on spermatogenesis harm not only humans but also livestock and aquatic life. As a result, efforts are being made to remove it from the ecosystem. A microorganism that can convert soluble molybdenum into colloidal molybdenum blue has been discovered. Phosphate concentrations were optimum between 2.5 and 5, molybdate concentrations between 15 and 20, pH between 6, and temperature between 25 and 34 degrees Celsius for the bacteria to thrive. Absorption spectrum of Mo-blue shows a peak at 865 nm and a shoulder at 700 nm, which indicates that it is in fact reduced phosphomolybdate. Copper, mercury, silver, copper, and chromium are all hazardous heavy metals that hinder the synthesis of Mo-blue. Bacillus sp. strain Zeid 15 is the most likely candidate for the bacterium's identity. As part of our screening, we look for the bacterium's capacity to employ different nitriles and amides as potential electron donors for molybdenum reduction or as substrates for growth. A microplate format was used for the screening. The bacterium was able to use the amides acrylamide and propionamide as sources of electron donor for reduction. Mo-blue production was best supported by acrylamide between 750 and 1250 mg/L, and propionamide between 750 and 1000 mg/L. In addition, these amides including acetamide could support the growth of the bacterium. The modified Gompertz model was utilized to model the growth of this bacterium on amides. The modelâ€™s growth parameters obtained were lag periods of 1.372, 1.562 and 1.639 d and maximum specific growth rates of 1.38, 0.95 and 0.734 d-1, for acrylamide, acetamide and propionamide, respectively. The capacity of this bacterium to decontaminate simultaneously amides and molybdenum is a novel characteristic that will be very beneficial in bioremediation.
Keywords: Molybdenum; Molybdenum blue; Bioremediation; Molybdenum reduction; Bacillus sp.